THE INFLUENCER PRICING PROGNOSTICATION ON SOCIAL MEDIA DYNAMICS AN ADVANCED EXAMINATION OF LINEAR REGRESSION 2 POLY DEGREE ALGORITHM & NEURAL NETWORK: AN ADVANCED EXAMINATION OF LINEAR REGRESSION 2 POLY DEGREE ALGORITHM & NEURAL NETWORK - Canesta, Felicia; Rusdianto Roestam (MUST, 2024)
The pervasive influence of social media has spawned the influencer profession, a potent force shaping audience interest in promoted products and services. Unlike traditional media, the impact of influencer promotion is quantifiable, with rates typically determined by factors such as follower count, engagement, and reach. However, the absence of a standardized reference for rate determination poses a potential risk of losses for both influencers and clients. This study seeks to address this challenge through the development of an advanced machine learning-based deep learning predictive model, incorporating Linear Regression with a second-degree polynomial algorithm and a neural network to enhance accuracy. This research underscores the potential of machine learning, including advanced regression algorithms and neural networks, in providing a robust framework for predicting influencer rates. The developed model serves as a significant step toward minimizing adverse effects on both influencers and clients by offering a more nuanced and accurate reference for rate determination in the dynamic landscape of social media promotion The Model Evaluation based on Mean Absolute Error (MAE) metrics reveals that the Keras Neural Network outperformed both Simple Linear Regression (10.612) and Linear Regression with a 2nd-degree polynomial (10.089) in predicting influencer rates. With a substantially lower MAE of 7.952, the neural network demonstrated superior accuracy, leveraging its capacity to capture intricate data relationships and learn non-linear patterns. In conclusion, the Keras Neural Network emerges as the most effective model for influencer rate prediction. Pengaruh meresap dari media sosial telah melahirkan profesi sebagai seorang influencer, kekuatan yang signifikan membentuk minat audiens terhadap produk dan layanan yang dipromosikan. Berbeda dengan media tradisional, dampak promosi influencer dapat diukur dengan jelas, dengan tarif yang umumnya ditentukan oleh faktor-faktor seperti jumlah pengikut, keterlibatan, dan jangkauan. Namun, ketiadaan referensi standar untuk penentuan tarif menimbulkan risiko potensial kerugian bagi influencer dan klien. Penelitian ini bertujuan untuk mengatasi tantangan ini melalui pengembangan model prediktif deep learning berbasis machine learning yang canggih, yang mencakup Regresi Linier dengan algoritma polinomial derajat kedua dan jaringan saraf untuk meningkatkan akurasi. Penelitian ini menegaskan potensi machine learning, termasuk algoritma regresi canggih dan jaringan saraf, dalam menyediakan kerangka kerja yang kokoh untuk memprediksi tarif influencer. Model yang dikembangkan merupakan langkah signifikan untuk meminimalkan efek negatif pada kedua belah pihak, influencer dan klien, dengan memberikan referensi yang lebih nuanced dan akurat untuk penentuan tarif dalam dinamika promosi media sosial. Evaluasi Model berdasarkan metrik Mean Absolute Error (MAE) menunjukkan bahwa Keras Neural Network mengungguli baik Simple Linear Regression (10,612) maupun Linear Regression dengan polinomial derajat kedua (10,089) dalam memprediksi tarif influencer. Dengan MAE yang jauh lebih rendah, yakni 7,952, jaringan saraf menunjukkan akurasi yang superior, memanfaatkan kapasitasnya untuk menangkap hubungan data yang rumit dan belajar pola non-linear. Sebagai kesimpulan, Keras Neural Network muncul sebagai model paling efektif untuk memprediksi tarif influencer.